Interstitial lung disease increases susceptibility to and severity of COVID-19 - Lee, Hyun; Choi, Hayoung; Yang, Bumhee; Lee, Sun-Kyung; Park, Tai Sun; Park, Dong Won; Moon, Ji-Yong; Kim, Tae-Hyung; Sohn, Jang Won; Yoon, Ho Joo; Kim, Sang-Heon (The European respiratory journal, 2021)
There are limited data regarding the relationship between interstitial lung disease (ILD) and the natural course of coronavirus disease 2019 (COVID-19). In this study, we investigate whether patients with ILD are more susceptible to COVID-19 than those without ILD and evaluate the impact of ILD on disease severity in patients with COVID-19. A nationwide cohort of patients with COVID-19 (n=8070) and a 1:15 age-, sex-, and residence-matched cohort (n=121 050) were constructed between January 1, 2020 and May 30, 2020 in Korea. We performed a nested case-control study to compare the proportions of patients with ILD between the COVID-19 cohort and the matched cohort. Using the COVID-19 cohort, we also evaluated the risk of severe COVID-19 in patients with ILD those without ILD. The proportion of patients with ILD was significantly higher in the COVID-19 cohort than in the matched cohort (0.8% 0.4%, p<0.001). The odds ratio [OR] of having ILD was significantly higher in the COVID-19 cohort than in the matched cohort (adjusted OR=2.02, 95% confidence interval [CI]=1.54-2.61). Among patients in the COVID-19 cohort, patients with ILD were more likely to have severe COVID-19 than patients without ILD (49.3% 13.1%), including mortality (13.4% 2.8%) (all p<0.01). The risk of severe COVID-19 was significantly higher in patients with ILD than in those without ILD (adjusted OR=2.32, 95% CI=1.24-4.01). The risks of COVID-19 and severe presentation were significantly higher in patients with ILD than in those without ILD.